A Method to Predict Specific Types of Violence Against Women in Pernambuco - Xavier, Arthur Carvalho da S.; Rodrigues, Cleyton M. de Oliveira (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2025: Anais do XXII Encontro Nacional de Inteligência Artificial e Computacional, 2025)
This study presents the main observations on the use of Machine Learning algorithms to predict specific types of violence against women in the state of Pernambuco. Only in 2024, more than 30.000 cases of gender-based violence were reported, with more than 100 resulting in homicide, in addition to serious harm to women’s health. Therefore, the objective of the study is to find the best models for predicting specific types of violence to mitigate future cases. To this end, data from the Ministry of Women from 2015 to 2021 were used, in addition to tests with different Machine Learning models, resulting in models with accuracy and precision above 70% and 75%, respectively. In addition, an interpretability analysis was performed to identify bias in the best model.